Triple A (Allgrove) Syndrome in a 5-Year-Old Male: A Novel Paediatric Case of Diagnostic Delay - Saba Noor, Mahad Younas (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Triple A syndrome (Allgrove syndrome) is an extremely rare inherited disease that affects multiple body systems. It is defined by three main features: absence of tears (alacrimia), adrenal gland failure that does not respond to ACTH, and difficulty in swallowing due to a tight lower esophagus (achalasia cardia). First reported in 1978, the condition affects about 1 in every 1,000,000 people and shows a wide range of symptoms. Due to its uncommon nature and the involvement of various organs, making an early diagnosis is often difficult, especially in areas with limited healthcare resources. Objective: To present a diagnostically complex pediatric case of triple A syndrome and emphasize the significance of earlier identification and a collaborative approach in treating this serious condition. Materials and Methods: A comprehensive retrospective examination was performed on the clinical progression of a 4.5-year-old boy who arrived at the Pediatric Surgery Department of Khyber Teaching Hospital in Peshawar. We thoroughly assessed the patient's history, examination results, biochemical analysis, imaging studies, esophageal tests (manometry and endoscopy), treatment plan, and follow-up. Results: The patient showed signs of frequent vomiting, poor growth, difficulty swallowing, and lack of tears. He had been incorrectly diagnosed with tuberculosis before and underwent extended anti-tubercular treatment with no progress. Hormonal assessment showed reduced cortisol and increased ACTH, signaling adrenal insufficiency. Esophageal manometry and EGD verified achalasia, which was managed through Heller's myotomy. The classical triad of alacrimia, achalasia, and adrenal insufficiency resistant to ACTH culminated in the diagnosis of Triple A syndrome. Multidisciplinary management led to significant clinical enhancement. Conclusion: This case highlights the importance of a strong suspicion for Triple A syndrome in children exhibiting unexplained gastrointestinal, ocular, or endocrine symptoms. Timely diagnosis and treatment avert significant complications and enhance results.